Proxies for paleo-oxygenation: A downcore comparison between benthic foraminiferal surface porosity and I/Ca - Lu, W; Barbosa, CF; Rathburn, AE; Xavier, PDM; Cruz, APS; Thomas, E; Rickaby, REM; Zhang, YG; Lu, Z (Elsevier, 2021)
Benthic foraminiferal surface porosity (the mean percentage of surface area covered by pores; higher porosity: lower oxygenation) and iodine to calcium ratio (I/Ca, higher I/Ca: higher oxygenation) are both promising paleoceanographic proxies that will advance through testing in down-core studies. Here we report the first down-core comparison (~45 kyr) of these proxies for a core from the southern Brazilian margin (26°40.22′ S, 46°26.46′ W, 475 m water depth). Both proxies are most sensitive to low-O2 conditions (<50 μmol/kg), and not well-constrained at higher O2 concentrations. Porosity values are generally low (<15%) and I/Ca ranges between ~4 and ~ 6 μmol/mol throughout the core. The two proxies are overall consistent, suggesting that bottom-water oxygen concentrations at the site remained above 50 μmol/kg during the last 45 kyr. Several non-O2 factors (e.g., iodate reduction rates, water mass mixing, temperature, foraminiferal shell robustness) could influence the proxies and require further investigation.